2014
DOI: 10.1109/tps.2014.2333772
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Deposition of Diamond at Low Pressures: A Review

Abstract: Plasma deposition techniques of nanocrystalline and microcrystalline diamond and related mechanisms at pressures below 0.1 torr are reviewed. The mechanism of nucleation and growth of diamond in low-pressure conditions is discussed theoretically and experimentally along with the role of radicals and ions in two different ion-energy ranges. For ion impact energies below 20-30 eV, diamond deposition occurs on a surface. The growth process is limited by the substrate temperature and the flux of hydrogen radicals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 78 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…18,19 To date, it has been reported that thin lms with novel nanostructure could be prepared with macro superlubricity properties through plasma vacuum deposition technology. [20][21][22] However, extreme conditions or high energy preparation methods are necessary to synthesize these nanostructures; for example, graphene, 23,24 nanotube, 25,26 nanodiamonds, 27 and fullerene 28 can only be fabricated at high temperature, with high energy ions states, or with catalysts, and nanocrystallitesembedded amorphous carbon require methods such as modi-ed arc techniques. [29][30][31][32][33] Thus, the growth energy greatly impacts the formation of the nanostructured carbon.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 To date, it has been reported that thin lms with novel nanostructure could be prepared with macro superlubricity properties through plasma vacuum deposition technology. [20][21][22] However, extreme conditions or high energy preparation methods are necessary to synthesize these nanostructures; for example, graphene, 23,24 nanotube, 25,26 nanodiamonds, 27 and fullerene 28 can only be fabricated at high temperature, with high energy ions states, or with catalysts, and nanocrystallitesembedded amorphous carbon require methods such as modi-ed arc techniques. [29][30][31][32][33] Thus, the growth energy greatly impacts the formation of the nanostructured carbon.…”
Section: Introductionmentioning
confidence: 99%
“…In typical subplantation processes, ions can penetrate into the subsurface region of a film . The film density is balanced between the density increment by ion‐induced condensation and the density relaxation by ion‐induced damage . Above a threshold ion energy (~20 to 30 eV for amorphous carbon and boron nitride), a lower ion energy would be better to increase the film density as well as the order and crystallinity of sp 2 phase because of minimal damage.…”
Section: Resultsmentioning
confidence: 99%
“…Low pressure plasma treatment is used widely in material processing. For example for plasma etching in the semiconductors industry [39] as well as the deposition of coatings such as diamond like carbon (DLC) for tribological applications [40]. For polymer processing low pressure plasmas are used in applications ranging from achieving enhanced adhesion, for contaminant removal, and for coating deposition, i.e.…”
Section: Low Pressure and Atmospheric Pressure Plasmasmentioning
confidence: 99%